Climate change can disrupt ecological interactions in mysterious ways: Using ecological generalists to forecast community-wide effects - Fontúrbel, Francisco E. (2021)
Ecological interactions are the backbone of biodiversity. Like individual species, interactions are threatened by drivers of biodiversity loss, among which climate change operates at a broader scale and can exacerbate the effects of land-use change, overharvesting, and invasive species. As temperature increases, we expect that some species may alter their distribution towards more amenable conditions. However, a warmer and drier climate may impose local effects on plants and animals, disrupting their interactions before noticeable changes in distribution are observed. We used a mutualistic trio from the temperate forests of South America to theoretically illustrate how climate change can disrupt ecological interactions, based on our current knowledge on this system. This study system comprises three generalist species with intersecting roles: a keystone mistletoe, a pollinator hummingbird, and a frugivorous marsupial that disperses the seeds of many species. On the one hand, drought causes water stress, increasing mortality of both mistletoe and host plants, and reducing the production of flowers and fruits. These resource shortages negatively impact animal's foraging opportunities, depleting energy reserves and compromising reproduction and survival. Finally, warmer temperatures disrupt hibernation cycles in the seed-dispersing marsupial. The combined result of these intersecting stressors depresses interaction rates and may trigger an extinction vortex if fail to adapt, with deep community-wide implications. Through negatively affecting generalist mutualists which provide resilience and stability to interaction networks, local-scale climate impacts may precipitate community-wide extinction cascades. We urge future studies to assess climate change effects on interaction networks rather than on singular species or pairwise partnerships.